Renal autotransplantation to treat renal artery aneurysm: case report - Genzini, Tercio (2014)
CONTEXT: Renal artery aneurysm (RAA) is uncommon and usually asymptomatic, but complications like rupture or thromboembolism of the aneurysm can occur, with consequent renal infarction. Most of the clinical findings are found incidentally through imaging examinations, in investigating other diseases. Renal autotransplantation (RAT) is an alternative treatment for complex RAA, with satisfactory results described in the literature. CASE REPORT: The patient was a 48-year-old man with a history of systemic arterial hypertension, thrombocytopenia and advanced hepatosplenic schistosomiasis. He complained of right lumbar pain, which was investigated through imaging examinations (computed tomography and angiotomography). These revealed right RAA of 2.5 cm in diameter. Evaluation by the vascular surgery team found that this was untreatable using endovascular methods. The treatment performed was open right nephrectomy with kidney preservation in solution, followed by aneurysmectomy, suturing of the injured artery and kidney reimplantation in the right iliac fossa with anastomosis of the iliac vessels and ureter. The durations of the surgery and kidney ischemia were 385 and 140 minutes, respectively. The patient was discharged on the 20th postoperative day, with creatinine concentration of 1.4 mg/dL, urea 41 mg/dL, urine volume 1400 mL/24 h and ascites treated with diuretics. CONCLUSION: RAT is indicated basically in three situations: extracorporeal reconstruction of complex aneurysms of the renal pedicle, extensive ureteral injury, and conservative kidney cancer surery in patients with a single kidney. This study presents a case of a patient with advanced liver disease and RAA that was untreatable using endovascular methods and was successfully treated using RAT.